2015
DOI: 10.15197/sabad.1.12.16
|View full text |Cite
|
Sign up to set email alerts
|

Headscarf Pin Localized in the Right Main Bronchus and Two Pins in the Abdomen

Abstract: Tracheobronchial foreign body aspiration is a serious condition that might result in mortality and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…A general male predominance for FBA has been reported by many authors, while scarf pin aspiration occurs uniquely in female patients; no reports have described male patients. 5 15 Our study was consistent with this finding in that all patients were female.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A general male predominance for FBA has been reported by many authors, while scarf pin aspiration occurs uniquely in female patients; no reports have described male patients. 5 15 Our study was consistent with this finding in that all patients were female.…”
Section: Discussionsupporting
confidence: 90%
“…Our literature review showed that the mean age of this population is 13 to 20 years. 5 , 6 , 7 , 9 In the present series, the patients’ ages ranged from 8 to 30 years with a mean age of 15.74 years. The occurrence of scarf pin aspiration in older patients compared with other types of FBA can be explained by the fact that this accident occurs mostly in young Muslim girls who have newly started wearing hijabs.…”
Section: Discussionmentioning
confidence: 76%
“…Diagnosis is usually straightforward via a history and the presence of the radio-opaque pin on a chest X-ray. For proximally located pins in the trachea and main bronchi, the treatment is extraction using a rigid bronchoscope and less commonly a fl exible bronchoscopy [8].…”
Section: Discussionmentioning
confidence: 99%